Redesigning Productivity and Skills: Dynamics of Migrant Work Force and Emergence of Strengthened Rural Indian Economy Post Covid-19 Pandemic (IITM Journal of Business Studies, 2024)
India is experiencing extensive transformational  changes in rural economy alongside  transformations in its overall national economy.  Conventionally, agriculture is judged as the  leading segment of rural economy including  rural employment in India. Frequent movement  of workers between a variety of jobs and  between informal and formal sections of rural  economy have been observed in the past.  (ILO Department of Statistics, 2011). Around  forty per cent of land available for cultivation  comprises of semi-arid tropics (SAT) where  agriculture is generally a one-season activity. As  a consequence, rural agricultural workers engage  in rural non-farm activities within their village  or else seasonally travel to urban cities to obtain  employment.
Keywords: agriculture; economy; including